Journey Into Agroforestry Youth Activity Book - Julie Clingerman; Alan Long; Joy Cantrell Jordan; Laura Lok (EDIS)
The activities in this book ask you to explore your community, ask questions, seek information, and create potential land management plans. Each activity and many of the challenges are designed to help you practice important life skills while learning how to think of alternative solutions to current land management challenges through agroforestry. This information was published June 2005 as 4-H FOM 14, Florida Cooperative Extension Service.